Effects of game performance on softball pitchers and catchers - Oliver, G. D.; Plummer, H. A.; Washington, J. K.; Weimar, W. H.; Brambeck, A. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to examine the effects of game exposure on pitchers and catchers' hip and glenohumeral range of motion (ROM), isometric strength, and vertical jump performance and power. Five college female softball pitchers (174.24 ± 7.53 cm; 82.10 ± 11.27 kg; 20 ± 1.82 years) and 4 catchers (165.10 ± 9.04 kg; 68.61 ± 3.87 cm; 20 ± 1.41 years) participated. Hip and glenohumeral rotational ROM; hip and glenohumeral rotational isometric strength; hip abduction and adduction strength; and vertical jump height were assessed pre- and postgame exposure. The catchers displayed significantly greater throwing side hip internal rotation (IR) ROM (mean difference = +6.88°, p = 0.03) postgame exposure, whereas the pitchers exhibited less IR (mean difference = -2.02%, p = 0.013) and external rotation (ER; mean difference = -1.95%, p = 0.026) strength in the nonthrowing side hip pre vs. postgame exposure. The performance demands of pitchers and catchers vary greatly, causing position-specific decreases/increases in various tests following game performance. Pitchers exhibited significant decreases in nonthrowing side hip IR and ER strength. In catchers, throwing side hip IR ROM significantly increased following game exposure. Further evaluation of ROM, strength, and power is necessary as it is unknown how these changes following a game affect sports performance or risk of injury.